Prawo bez autorytetu – prawo pozbawione sumienia... - Bałandynowicz, Andrzej (Horyzonty Wychowania, 2017)
Andrzej Bałandynowicz’s text takes up the central topic ofconscience in the context of the existing condition of law in Poland.Law „without conscience” is, according to the author’s analyses,the effect of a gap the system of formal regulations andthe universal system of moral beliefs shared by the society. Thefundamental demand here is then the return to law finding itsroots in morality. In this way it will regain authority, indispensablealso as far as its actual effectiveness is concerned. The author’sreflection is focused on specific, binding legal solutions within thescope of social service activity and criminal responsibility systemfunctioning. In both cases, the deficiencies – contrary to the functionsdeclared – result in the deepening of segregation and socialexclusion of individuals processes.